"Solve 6x^2=-3x-2 using the quadratic formula.?"
That sounds like an excellent idea.
First, set it to zero:
6x^2 = -3x - 2 becomes
6x^2 + 3x + 2 = 0
Plug that into the quadratic equation.
2007-09-04 06:56:30
·
answer #1
·
answered by Brian L 7
·
1⤊
0⤋
Get it into the form of ax^2 + bx + c = 0, and apply the formula:
x = [-b ± â(b^2 - 4ac) ] / 2a
So 6x^2 + 3x + 2 = 0, and
x = [ - 3 ± â(9 - 4(6)(2)) ] / (2*6)
You get a value less than zero underneath the square root, so there is no real solution. If you've already learned about imaginary numbers in class, then write the two complex roots. Otherwise, there's "no solution".
2007-09-04 13:56:11
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
6x^2=-3x-2
6x^+3x+2=0
a = 6, b= 3, c= 2
x= [-b +/- sqrt(b^2-4ac)]/2a
x = [-3 +/- sqrt(3^2-4*6*2)]/(2*6)
x = [-3 +/- sqrt(-39)]/12
x = [-3 +/- isqrt(39)]/12
So the solution is imaginary. The function never crosses the x-axis.
2007-09-04 14:12:59
·
answer #3
·
answered by ironduke8159 7
·
0⤊
0⤋
6x^2+3x+2=0
we have a=6,b=3 & c=2
x={-3+-sq rt(3^2-4.6.2)}/2.6
or x={-3+-sq rt(9-48)}/12
or x={-3+-sq rt(-39)}/12 ans
2007-09-04 14:15:04
·
answer #4
·
answered by MAHAANIM07 4
·
0⤊
0⤋